Gambaran Perawatan Perineal Pada Bayi Dengan Diaper Rast di PMB Santi Rahayu Jabung Kabupaten Malang - Sera Dea Permata; Tarsikah Tarsikah; ita yuliani (Poltekkes Kemenkes Malang, 2020)
Diaper Rash is one of the problems that arise in the baby skin due to the incorrect treatment of the perineal area. The worst impact of incorrect treatment perineal care can disrupt the growth process, so it is necessary to give an intens good treatment, especially the perineal area of the baby in order to avoid problems such as Diaper Rash. The purpose of this study was to determined the description of perineal care in infants with diaper rash at PMB Santi Rahayu Jabung Malang Regency. This study using Qualitative descriptive research method with a case study approach. The method of geting respondens with a purposive sample of 4 mothers who have babies with diaper rash, 3 baby grandmothers, and 1 baby aunt who lives together as familly and involved in daily care of the baby. The validity of the data uses source triangulate method. The instrument that used in this study is the guideline for in depth interviews and the results from mobile voice recordings as documentation in the study. The result of this study showed that mothers treated their perineal babies before Diaper Rash by using pampers diapers longer than cloth diapers, changing brands of pampers, using fragrance softeners when washing diapers and baby clothes, changing pampers more than four hours, does not dry the perineal area after cleaning, use powder to the perineal area, change the brand of bath soap